2016
DOI: 10.15345/iojes.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Teachers’ Locus Of Control And Job Satisfaction: A Mixed Method Study

Abstract: The aim of this study is to reveal the relationship between locus of control and job satisfaction perceptions of teaches working in state schools of Tire/İzmir through both qualitative and quantitative perspective. Study group pf the study is the teachers working in Tire/İzmir in 2015-2016 academic calendar. The quantitative data of the research have been obtained through 'Personal Information Form' and 'Multidimensional Locus of Control Scale' developed by Levenson (1974) and adapted to Turkish by Kıral (2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The fact that job satisfaction can be significantly predicted by the LOC is valid also for schoolteachers (Basak & Ghosh, 2011). Akkaya and Akyol (2016) found that teachers' perception of ILC is lower than their perception of LOC based on others and luck/faith. Akca et al (2018) tested relationships among self-efficacy beliefs, LOC, and intercultural sensitivities among teachers.…”
Section: Loc In Education-oriented Professionsmentioning
confidence: 85%
“…The fact that job satisfaction can be significantly predicted by the LOC is valid also for schoolteachers (Basak & Ghosh, 2011). Akkaya and Akyol (2016) found that teachers' perception of ILC is lower than their perception of LOC based on others and luck/faith. Akca et al (2018) tested relationships among self-efficacy beliefs, LOC, and intercultural sensitivities among teachers.…”
Section: Loc In Education-oriented Professionsmentioning
confidence: 85%
“…The perception teachers had of internal locus of control was found to be lower than the locus of control based on others, and luck or faith. Conversely, the perception of internal job satisfaction was perceived higher than the external one (Akkaya & Akyol, ). No relationship was found between job satisfaction and self‐efficacy, and no significant relationship was observed between a sense of efficacy and the spiritual well‐being of the teachers (Rastegar & Moradi, ).…”
Section: Resultsmentioning
confidence: 99%
“…Further research studies should therefore be conducted for more understanding and validation of the phenomenon and the findings (Hsing‐Ming et al , ). A prime suggestion was that teachers should be made responsible to take decisions related to their profession (Akkaya & Akyol, ). Another prime suggestion was to conduct this same study with a large number of participants for further validity, reliability and generalisability of the results, looking at factors such as age, gender, experience, etc.…”
Section: Recommendations and Solutionsmentioning
confidence: 99%
“…Some of studies, in the literature, which related with locus of control and job satisfaction showed that locus of control is an important issue for job (Gangai et al, 2016;Akkaya and Akyol, 2016). Ahn investigated how a worker's locus of control affects job-to-job and job-to-non employment turnover (Ahn, 2015).…”
Section: Locus Of Controlmentioning
confidence: 99%